Association of Dietary Intake of Flavonols With Changes in Global Cognition and Several Cognitive Abilities. (14th February 2023) - Holland, Thomas Monroe; Agarwal, Puja; Wang, Yamin; Dhana, Klodian; Leurgans, Sue E.; Shea, Kyla; Booth, Sarah L.; Rajan, Kumar B.; Schneider, Julie A.; Barnes, Lisa L.
Abstract : Background and Objectives: Previous research has examined the association between cognition and flavonoids: bioactives found in foods, known to possess anti-inflammatory and antioxidant properties. We extend this research by investigating associations of dietary intakes of total flavonols and constituents (kaempferol, quercetin, myricetin, and isorhamnetin) on the change in cognitive performance in global cognition, episodic memory, semantic memory, visuospatial ability, perceptual speed, and working memory. Methods: The study was conducted using 961 participants (aged 60–100 years) of the Rush Memory and Aging Project, a prospective cohort of community-dwelling Chicagoans who were followed for an average of 6.9 years. Diet was assessed using a validated semiquantitative food frequency questionnaire. Cognitive performance was assessed annually with a battery of 19 standardized tests. Flavonol intake was analyzed as a continuous variable using linear mixed-effects models. Cognitive domain scores were regressed on baseline calorie-adjusted flavonol variables. Results: Higher dietary intakes of total flavonols and flavonol constituents were associated with a slower rate of decline in global cognition and multiple cognitive domains. In continuous models adjusted for age, sex, education, APOE ɛ4, late-life cognitive activity, physical activity, and smoking, total flavonol intake was associated with slower decline in global cognition β estimate = 0.004 (95% CI 0.001–0.006), episodic memory β = 0.004 (95% CI 0.002–0.006), semantic memory β = 0.003 (95% CI 0.001–0.007), perceptual speed β = 0.003 (95% CI 0.001–0.004), and working memory β = 0.003 (95% CI 0.001–0.005) and marginally associated with visuospatial ability β = 0.001 (95% CI −0.001 to 0.003). Analyses of individual flavonol constituents demonstrated that intakes of kaempferol and quercetin were associated with slower global cognitive decline (β = 0.01 [95% CI 0.006–0.02] and β = 0.004 [95% CI 0.0005–0.007]), respectively. Myricetin and isorhamnetin were not associated with global cognition. Discussion: Results suggest that dietary intakes of total flavonols and several flavonol constituents may be associated with slower decline in global cognition and multiple cognitive abilities with older age.